2017
DOI: 10.1097/md.0000000000006674
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent laryngeal nerve injury after thyroid and parathyroid surgery

Abstract: Recurrent laryngeal nerve (RLN) injury is a feared complication after thyroid and parathyroid surgery. It induces important postoperative morbidity. The present study aimed to assess the incidence of transient/permanent postoperative RLN injuries after thyroid and parathyroid surgery in the present cohort, to observe the timing of recovery, and to identify risk factors for permanent RLN injury after thyroidectomy.All consecutive patients operated on at our institution for thyroid and parathyroid pathologies fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
4
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(131 citation statements)
references
References 22 publications
6
104
4
4
Order By: Relevance
“…According to our results, the incidence of new VFP was 53 in 920 (5.8%) operations and 55 in 1296 (4.2%) nerves at risk. Compared to the results of previous studies in which routine laryngoscopy was used [4,5], our complication rate was lower (5.8% against 7.6-13.9%). On the other hand, we observed much higher rate of permanent VFP than was demonstrated in these previous studies (3.2-3.4% against 0.9-1.4%).…”
Section: Discussioncontrasting
confidence: 85%
“…According to our results, the incidence of new VFP was 53 in 920 (5.8%) operations and 55 in 1296 (4.2%) nerves at risk. Compared to the results of previous studies in which routine laryngoscopy was used [4,5], our complication rate was lower (5.8% against 7.6-13.9%). On the other hand, we observed much higher rate of permanent VFP than was demonstrated in these previous studies (3.2-3.4% against 0.9-1.4%).…”
Section: Discussioncontrasting
confidence: 85%
“…These causes were found in previous studies with different range of incidence. [3,[29][30][31][32][33][34] Idiopathic cause of vocal fold paralysis was found in 19 cases (17.9%). This finding is in conjugation with literature; Al-Khtoum N et al found that the incidence of idiopathic vocal fold paralysis was 18.9%.…”
Section: Discussionmentioning
confidence: 99%
“…The right recurrent laryngeal nerve [1] The right and left nerves are not symmetrical. The right RLN is shorter and makes a quick entry and exit at the apex of the right chest.…”
Section: Functionmentioning
confidence: 99%
“…The RLN remains in the tracheooesophageal groove heading up and out of the thoracic inlet. In the neck, the RLN cannot help but annoy thyroid surgeons before reaching its final destination [1]. The thoracic surgeon encounters the ascending left RLN when performing Mediastinoscopy.…”
Section: Surgical Exposure Of the Right Rlnmentioning
confidence: 99%
See 1 more Smart Citation